2015
DOI: 10.1590/s1517-707620150002.0054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on hardness and wear behavior of weld deposited Co-Cr-Mo alloy

Abstract: Metallic materials are generally characterized by the evaluation of hardness and wear resistance of the material at the specified condition. The characterization is necessary for understanding the behavior of the metals, especially alloys, at different conditions. To study the effect of heat treatment on weld deposited Co-Cr-Mo alloy, arc welding process has been used to prepare the samples.Using L9 Orthogonal array of Taguchi method, the samples, in three groups,are heat treated by solution at 1200 o C for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
2
0
0
Order By: Relevance
“…It is observed that as the percentage of reinforcement increases the area fraction also increases as shown in the micrographs. Similar trends have been observed by many other researchers [11].…”
Section: Microstructure Evaluation Of the Welded Specimenssupporting
confidence: 92%
See 1 more Smart Citation
“…It is observed that as the percentage of reinforcement increases the area fraction also increases as shown in the micrographs. Similar trends have been observed by many other researchers [11].…”
Section: Microstructure Evaluation Of the Welded Specimenssupporting
confidence: 92%
“…It is observed that the hardness values of the material are directly proportional to the presence of ZrO 2 and with the increase in ZrO 2 , the hardness value of the composites increases .The above graph shows the variation of Brinell hardness value for different compositions of ZrO 2 in LM25/ZrO 2 composites. Similar trends have been observed by many other researchers [11,13].…”
Section: Effect Of Hardnesssupporting
confidence: 92%